Bureaucratic Rationalism and The Quiet (R)evolution - William Twining (Legal Education Review)
[Extract] We do something called teaching. But we all know from bitter personal experience that nothing is, or can be, taught once we get beyond the communication to small children of the basic mysteries on which civilization depends — how to read, how to write, how to count. We can of course pump students full of facts or even brainwash them — but pumping facts is a waste of everybody’s time and washing brains in public is, as Justice Holmes might have told us, dirty business. Learning is what students are there for and all we know about learning is that, on any level of complexity, it is every man for himself and by himself, imposing a perhaps delusive formal pattern on the swirling chaos by a prodigious effort of the individual will. It may be that we can stimulate, or irritate, an occasional student into undertaking this arduous task — but, if we do so, it will be much more by accident than by our own design. Karl Llewellyn once observed that the function of the law teacher is not to let the true light shine; he was wise to content himself with that negative formulation. Grant Gilmore